Mastering Teaching English for Young Learners - Fajarina, Maskhurin (Universitas Islam Madura, 2017)
Teaching language to old learners is different from teaching language to young learners. Young learners have certain characteristics which are different from old learners so those influence their acquiring a foreign language. Teaching foreign language is easy if we understand the rules well. The rules are understanding characteristics of our students, mastering some suitable methods, and choosing a suitable material. Young learners have certain characteristic distinguishing to the older learners. Related to the certain characteristics, the teacher must understand to differentiate the method they use in teaching English as a foreign language to the young learners. To empower the teaching, the teacher must master the material well.